Telemonitoring and quality of life in patients after 12 months following a pacemaker implant: The Nordland study, a randomised trial - Lopez-Liria, Remedios; Lopez-Villegas, Antonio; Enebakk, Terje; Thunhaug, Hilde; Lappegård, Knut Tore; Catalán-Matamoros, Daniel (International Journal of Environmental Research and Public Health, 2019)
Source at https://doi.org/10.3390/ijerph16112001. The purpose of this study was to analyse the health-related quality of life (HRQoL) of patients followed up using a remote device-monitoring system (TM) compared to patients followed up through standard outpatient visits (HM), 12 months after the implantation of a pacemaker. This was a trial design that used the EuroQol-5D Questionnaire and the Minnesota Living with Heart Failure Questionnaire (MLHF). The HRQoL of a cohort of 50 consecutive patients randomly allocated to one of the two follow-up modalities was measured at baseline and then during follow-up, 12 months after the pacemaker implantation. Eventually, 23 patients were followed-up through standard outpatient visits, while 23 used a remote monitoring system. Results: The baseline clinical characteristics and health-related quality of life of the patients from both groups were observed to be statistically similar. Twelve months after the pacemaker implantation, both groups showed statistically significant improvements in the baseline parameters based on the MLHF. The patients followed up through hospital visits showed a greater increase in MLHF-HRQoL after 12 months, although the increase was not significantly greater than that of the TM group. Furthermore, the frequencies of emergency visits and re-hospitalisations did not differ between the groups.